コウイド チタイ ニ オケル ホウシャセイ コウブツ タンサ - 奥野, 孝晴; オクノ, タカハル; 佐久間, 秀樹; サクマ, ヒデキ; Okuno, Takaharu; Sakuma, Hideki (1983)
P(論文) カナダの高緯度地帯では, 冬期の極地に特有な自然条件のもとでウラン鉱床の鉉が行われている。南極地域における放射性鉱物探査を露岩地域, あるいは氷雪による被覆がきわめて薄い地域に限定して実施するならば, 基本的にはカナダの高緯度地帯で用いられている各種の地球科学的探査法を適用することが可能である。概査の第1段階としては, 中型ヘリコプターによる総合的な空中物理探査が, 南極地域においても特に有効であろうと考えられる。 Uranium exploration has been carried out in the northern part of Canada in winter where the natural conditions are rather critical. A number of geophysical and geochemical exploration techniques have been employed to delineate various kinds of uranium mineralization as well as favorable geological structures. Those techniques are considered to be applicable to radioactive mineral exploration in outcropping areas of Antarctica where thickness of the ice cover is minimum. Among those techniques, a combined airborne geophysical survey utilizing a medium-sized helicopter is highly recommendable for the reconnaissance stage of the activity. departmental bulletin paper